Production design - Hoang, Tran Chau (2018)
This final year project is about production design and visual development that includes three components. One story was hand-printed in 16 full illustrations and accompanied by two visual developments for an animated film and a comic. The Story of a Cricket is an illustrated story of “The adventures of a Cricket” presented in the form of a book and processed in woodcut technic combining with digital editing of book design and publication. The Steadfast Tin Soldier by Hans Christian Andersen is explored to digital painting and the Cat’s café is my personal visual development for a comic style that I develop through the years. This report is a documentation of the entire process that was explored during the creation of this visual development. The report contents would focus on the process of the research, inspirations, illustrations, character/ background design and the making of the artworks themselves.